Selected factors for triple jump preparation: A case study of an Olympic silver medalist - Alfano Moura, N.; Han, P.; de Paula Moura, L.; Wang, G.; Yuan, T. (International Journal of Sports Science & Coaching, 2023)
The People's Republic of China obtained at the 2020 Tokyo Olympic Games its best historical performance in the triple jump, thereby winning the silver medal. The objective of this case study was to present how evidence-based knowledge was applied to improve selected factors that may have contributed to this result. The factors included running speed, strength, muscle power, jumping technique, body composition, mental preparation, training organization, and recovery. Short training blocks, monitoring of training sessions and athlete's status, individualized tapering, use of activation sessions the day before competition, and postactivation performance enhancement strategies used in training and at the event were concepts followed during the preparation to the Games. Improved performance in field tests and power training was accompanied by positive changes in approach speed, run-up accuracy, and jumping technique, which, together with mental preparation, enabled two personal records to be set in the Olympic final. The results in the field tests were among the best ever reported and could constitute a benchmark for world-class triple jumpers.